Killing in self-defence - Leverick, Fiona (Oxford University Press, 2006)
This book is a comprehensive analysis of the criminal defence of self-defence from a philosophical, legal, and human rights perspective. The primary focus is on self-defence as a defence to homicide, as this is the most difficult type of self-defensive force to justify. Although not always recognised as such, self-defence is a contentious defence, permitting as it does the victim of an attack to preserve their life at the expense of another. If one holds that all human life is of equal value, explaining why this is permissible poses something of a challenge. It is particularly difficult to explain where the aggressor is, for reasons of non-age or insanity for example, not responsible for their action